Waqf financing of higher education in the arab world : a bibliographical survey and critical review of the related literature - Barakat, Ahmed K.M (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
The absence of sufficient literature could stimulate a debate and open opportunities for research to develop further interest in using Waqf as viable mode of financing education. This paper conducts a bibliography survey of Waqf literature written in the Arabic language, and critically reviews the related literature to Waqf-based education. With the help of field-study, 79 materials on waqf have been found. An analysis of the literature shows that a majority of the literature deals with waqf laws, both classical and modem. By ranking these literatures, the study shows that much attention appears to be paid to Waqf based education. The paper further suggests that more research should be held in the area of financing education through waqf, to mobilize additional resources for education in the Arab and Muslim World.